Papillary Thyroid Cancer Affecting Multiple Family Members: A Case Report and Literature Review of Familial Nonmedullary Thyroid Cancer - Khaled Ahmed Baagar; Buthina Ibrahim Alowainati (Case Reports in Endocrinology)
Familial nonmedullary thyroid cancer (FNMTC) represents 5–10% of NMTC cases. Many controversies are associated with the FNMTC, namely, the minimum required number of affected family members to define the condition, aggressiveness, prognosis, and treatment and screening recommendations. Moreover, the genetic basis of the FNMTC has not yet been identified. We report a family diagnosed with FNMTC and present a comprehensive literature review of the condition. The index case was a 26-year-old male who was diagnosed with locally advanced papillary thyroid cancer (PTC). Then, his family members became worried and asked for a neck ultrasound. Four of his six siblings, in addition to his father, were diagnosed with PTC. In addition, two of his cousins were diagnosed. The patient underwent total thyroidectomy with bilateral neck dissection, and he received 2 doses of radioactive iodine (100 mCi each). Furthermore, one of his siblings required a second surgery with repeated radioactive iodine therapy. The index case genetic screening and whole-exome sequencing did not show any abnormalities. Future genetic and clinical research should focus on kindred with 3 or more affected individuals for better identification of the FNMTC susceptibility genes and to better guide management and screening recommendations.